Synthesis of Gram‐Scale Ultrastable Mn‐Doped 2D Perovskites for Light‐Emitting Diodes. Issue 7 (22nd February 2021) - Hou, Lu; Zhu, Yihua; Zhu, Jingrun; Li, Xuyan; Zeng, Feng; Yang, Tingyu; Gong, Yiqin; Shen, Jianhua; Li, Chunzhong
Abstract: Mn‐doped 2D perovskites are emerging as good candidates for light‐emitting applications due to their excellent optical and electrical properties. Major synthetic routes, solid‐state grinding and high‐temperature solution synthesis, are extensively studied to prepare Mn‐doped 2D perovskites. However, complicated synthesis, small‐scale yields, and poor‐stability impede their widespread applications. Herein, a one‐step acid‐solution‐assisted method is exhibited for gram‐scale production of Mn‐doped 2D (C8 H17 NH2 )2 PbBr4 with a solid yield of 1.35 g products out of 3 mL solvent. After Mn‐doped 2D (C8 H17 NH2 )2 PbBr4 being stored in the air for 90 days, the photoluminescence (PL) quantum yield of powders has minor changes, showing good stability. Phosphor‐converted monochrome light‐emitting diodes (LEDs) are fabricated. After the LEDs work 6 h under a voltage of 3 V, their PL spectra have no obvious change, showing a great potential in optoelectronic devices. This study provides a new effective strategy for large‐scale synthesis of ultrastable Mn‐doped 2D perovskites, which is expected to provide inspiration for the industrial optoelectronic applications of perovskites. Abstract : A simple acid‐solution‐assisted method for gram‐scale production of Mn‐doped 2D (C8 H17 NH2 )2 PbBr4 with a solid yield of 1.35 g products out of 3 mL solvent is exhibited in this work. After as‐prepared powders are stored in the air for 90 days, the photoluminescence quantum yield of powders has minor changes, showing good stability.